DEVELOPMENT OF PHYSICS E-MODULES BASED ON KVISOFT FLIPBOOK MAKER APPLICATION ON CIRCULAR MOTION MATERIAL - Meylani, Evy (Universitas Negeri Medan, 2023)
This study aims to determine the level of feasibility, practicality and effectiveness of the physics e-module based on the Kvisoft Flipbook Maker application on Circular Motion material. The type of method used in this study is development or Research and Development (R&D) using the 4D model, but is limited to three stages: 1) define, 2) design and 3) develop. The research results based on the validation of material experts and media experts obtained a total score of 19.7, with an average of 4.92 and 16.78 with an average of 4.19